The important role of extremely low content of soluted Ce in the wide stacking faults formation in Al-Ce alloy. (June 2022) - Zhang, Chi; Peng, Peng; Gao, Haiyan; Wang, Yufei; Wang, Jun; Sun, Baode
Abstract: The performance of the material can be significantly improved by introducing stacking faults and nanotwins. However, introducing high-density stacking faults and twins into Al remains difficult due to its ultrahigh stacking-fault energy. In this study, it was discovered for the first time that the addition of Ce promotes the formation of stacking faults in Al. The broadening of stacking faults is attributed to the extremely low content of Ce in Al and the local stress concentration during the rolling process. The solubility at eutectic temperature was determined to be 0.0084at.%. The solid solution of Ce has a great influence on the stacking fault energy of Al, which is attributed to the solute Ce disturbing the lattice orientation and electronic environment of the matrix atoms. The local stress concentration in Al matrix near the eutectic Al11 Ce3 phase also provides a favorable condition for the formation of stacking faults. Graphical abstract: Image, graphical abstract